Nowhere to Run: A Review of the Political Economy of Migration, Identity and Xenophobic Violence in Zambia - Bbaala, Phineas; Mate, Njekwa (African Human Mobility Review, 2021)
Zambia is one of the Southern African countries that have not witnessed any serious bloody conflicts either in their post-independence eras or the periods hitherto. Consequently, the country has, over the years, provided refuge to many victims of ethnic and racial conflicts from other African countries, especially within the Sub-Saharan African region. However, Zambia faces the daunting challenge of sustaining interregional, interethnic and interracial harmony among its own indigenous groups and those identified as foreign immigrants. The April 2016 xenophobic looting of shops belonging to other African nationals by residents of Lusaka highlighted the intensification of ethnic and racial conflict in the country. Amid these identity conflicts, some commentators from different intellectual and other persuasions have tried to explain ethnic and racial identity problems in relation to primordial, constructive and instrumental theoretical underpinnings. This article goes further to draw a relationship between economic downturn and identity and xenophobic violence. The article draws arguments from a review of existing literature and empirical data.